Expression Of The Creative Function Of Ahura Mazda In “Akhunavad Ghats” - Urazova Rano Tashpulatovna (Genius Journals, 2024)
This article covers analysis the content of the 4-song of Ahkunavad Ghats in the “Avesta”, the holy body of the ancient religion of the Mazda Yasna, based by prophet Zarathushtra. It is going an attempt to define the essence of some stanzas Ghats, which has been kept motif to affirmation to the role of Zarathushtra as the Head (- Rātu, i.e “judges”) in the choice of the people the path of righteousness. In the face of opposition parties interested in preserving the old pagan customs of multi-religious was shower highlights the difficulties in establishing the foundations of religion, Zarathushtra single god Ahura Mazda.
Keywords: establishing; judges; foundations; Zarathushtra